Changes in the dominant assembly mechanism drive species loss caused by declining resources. (27th November 2015) - Thorn, Simon; Bässler, Claus; Bernhardt‐Römermann, Markus; Cadotte, Marc; Heibl, Christoph; Schäfer, Hanno; Seibold, Sebastian; Müller, Jörg
Abstract: The species–energy hypothesis predicts that more productive areas support higher species richness. Conversely, when resources are reduced, species richness is reduced. Empirical tests of whether extinctions are predominantly caused by environmental constraints or competitive exclusion are lacking. We experimentally reduced dead wood to c . 15% of the initial amount after a major windstorm and examined changes in assembly mechanisms by combining trait‐based and evolutionary species dissimilarities of eight taxonomic groups, differing in their dependence on dead wood (saproxylic/non‐saproxylic). Species richness and assembly mechanisms of non‐saproxylic taxa remained largely unaffected by removal of dead wood. By contrast, extinctions of saproxylic species were caused by reversing the predominant assembly mechanisms (e.g. increasing importance of competitive exclusion for communities assembled through environmental filtering or vice versa). We found no evidence for an intensification of the predominant assembly mechanism (e.g. competitive exclusion becoming stronger in a competitively structured community).